Incidence patterns of colorectal cancers in four countries of the Middle East Cancer Consortium (Cyprus, Jordan, Israel, and İzmir, Turkey) compared with those in the United States Surveillance, Epidemiology, and End Results Program - Eser, Sultan; Chang, Jenny; Charalambous, Haris; Silverman, Barbara; Demetriou, Anna; Yakut, Cankut; Nimri, Omar; Pavlou, Pavlos; Özgür, Suriye; Ziogas, Argyrious; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: There are wide variations in colorectal cancer (CRC) incidence across the world. Historically, the highest incidence rates have been reported historically in more developed countries; however, increasing trends have been seen in developing countries. Here, we present the CRC incidence pattern in Cyprus, Israel, Jordan, and İzmir, Turkey, which are countries of the Middle East Cancer Consortium (MECC). Materials and Methods: We analyzed 2005-2010 CRC data from population-based registries and calculated crude and age standardized rates for CRC, colon and rectum subsites, and annual percent changes (APCs) for trends. Results: The age-adjusted incidence rates (AAIRs) for CRC were the highest in Israeli Jews (IJ) (46.7 for males and 35.5 for females), which exceeded those of the USA Surveillance, Epidemiology, and End Result (SEER) program registries. In both sexes, AAIRs in Cyprus and Israeli Arabs (IA) were close to those in SEER registries. For both sexes, AAIRs in İzmir and Jordan were substantially lower than those in other registries. Statistically significant decreasing trends over time were observed in AAIRs for both sexes in the SEER program (APCs: males, -3.24% and females, -2.54%), whereas the trends varied within the MECC registries. There were decreasing AAIR trends for males in IJ and IA and for females in Cyprus and IJ; APC for females in IJ (-4.29%) was significant. Conversely, increasing trends with the significant APCs were observed in males in İzmir (2.43%) and Jordan (7.57%). Conclusion: MECC countries comprise both high- and low-risk populations for CRCs. However, increasing trends in low-risk populations have been alarming. Thus, the need for implementing tailored primary and secondary prevention programs in the region is essential. Cite this article as: Eser S, Chang J, Charalambous H, et al. Incidence patterns of colorectal cancers in four countries of the Middle East Cancer Consortium (Cyprus, Jordan, Israel, and İzmir, Turkey) compared with those in the United States Surveillance, Epidemiology, and End Results Program. Turk J Gastroenterol 2018; 29: 35-43.